Exploring teachers’ reactions to writing ‘Thinking Stories’ for enhancing critical and creative thinking - Preece, Abdul Shakour Duncan; Altabaa, Homam; Wan Yusoff, Wan Mazwati; Juperi, Juhasni Adila; Poad, Noor Lydia (2020)
Current Malaysian educational policy requires school teachers to include critical and creative thinking into their classrooms and assessment; however, few teachers have been properly trained to do this or even know what it means. The research looks into the idea of providing teachers with an approach for teaching critical and creative thinking as well as developing their own thinking skills by getting them to write 'thinking stories' for their subject specializations. Qualitative research methodology was used by means of interviews to explore teachers' understanding and application of critical and creative thinking, as well as eliciting their views about using thinking stories to teach critical and creative thinking to their students. Four informants who showed enthusiasm and enjoyment during the program elaborated on the benefits and challenges they experienced. The results produced four main themes namely: Benefits, Challenges, Satisfaction and Improvement of WTS. Participants acknowledged that WTS provided them with a new teaching method for CCT in a positive meaningful environment. The challenges they faced included overcoming caution when being creative; integrating philosophical concepts into their stories and a lack of fluency in English. A minority of teachers borrowed ideas from existing stories demonstrating a lack of originality. However, there was general satisfaction with the WTS program with some participants requesting guidance on literary elements for the purpose of story writing as well as the opportunity to work in groups using their mother tongue. In addition, respondents suggested training in COPI and information about the overall goals of the program prior to the workshop. Overall, the WTS approach represents a successful way to get teachers to produce short thinking stories for COPI that integrate values and promote their CCT in a fun and meaningful way.